Analysis of the Dynamics of Changes in the Coastline of Cirebon City in 2010-2025 Using Geographic Information System (GIS) Technology - Muhammad Andhika Syahputra; Mohd. Abi Rafdi (Jurnal Indonesia Sosial Teknologi, 2026)
Coastal areas are dynamic transition zones, experiencing continuous physical changes due to the interaction between natural processes and anthropogenic activities. As a coastal area on the north coast of Java, Cirebon City faces serious challenges related to shoreline dynamics influenced by sedimentation, abrasion, infrastructure development, and land use changes. This study aims to analyze the dynamics of shoreline change in Cirebon City during the period 2010–2025 using Geographic Information System (GIS) technology and remote sensing. This study applied a mixed-method approach that integrates spatial quantitative analysis and qualitative descriptive analysis. Multitemporal satellite imagery from Landsat 7 (2010 and 2015) and Sentinel-2 (2020 and 2025) was processed using the Normalized Difference Water Index (NDWI) algorithm to extract shoreline positions. Furthermore, the Digital Shoreline Analysis System (DSAS) method with End Point Rate (EPR) calculations was applied to determine the rate and spatial distribution of abrasion and accretion. The results of the study indicate that the Cirebon City coastline experienced significant spatial changes during the 15 years of observation, with accretion processes dominating most coastal segments. The average rate of shoreline change reached 5.66 meters/year, with the highest accretion rate of 40.95 meters/year and maximum abrasion of -4.63 meters/year. The most prominent changes occurred in Lemahwungkuk District, primarily due to sedimentation processes and anthropogenic activities such as coastal reclamation and port development. These findings confirm that the integration of GIS, remote sensing, and field observations provides an effective approach to monitoring shoreline dynamics and supporting sustainable coastal management planning in urban areas.